1998
DOI: 10.1080/080370598437349
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vascular Load on Plasma Endothelin-1, Cytokines and Catecholamine Levels in Essential Hypertensives

Abstract: In vitro studies demonstrated a relationship between ET-1 and basic Fibroblast Growth Factor (bFGF), and of bFGF with Platelet Derived Growth Factor (PDGF). The present study was carried out to investigate in vivo the behaviour after vascular stress of circulating ET-1, bFGF and PDGF, and catecholamines, and their relationship. In 12 healthy normotensives (NTs) and 15 essential hypertensives (Ehs) venous blood samples to determine circulating ET-1, bFGF and PDGF, and catecholamine (EPI and NE) levels were draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There are few data showing increases in circulating vasoconstrictor hormones during static exercise, but they have been obtained in subjects varying in age and health status. It was demonstrated, therefore, that static handgrip caused an increase in plasma vasopressin in healthy young men (Nazar et al 1989), and endothelin-1 in hypertensive patients (Cottone et al 1998), young normotensive offspring of hypertensive parents (Mangieri et al 1998) and patients with congestive heart failure (Mangieri et al 1997). On the other hand, we have recently demonstrated that static handgrip caused also an increase in the plasma adrenomedullin (ADM), which is a potent vasorelaxant probably involved in the fine blood pressure control counteracting the effect of vasoconstrictors.…”
Section: Introductionmentioning
confidence: 99%
“…There are few data showing increases in circulating vasoconstrictor hormones during static exercise, but they have been obtained in subjects varying in age and health status. It was demonstrated, therefore, that static handgrip caused an increase in plasma vasopressin in healthy young men (Nazar et al 1989), and endothelin-1 in hypertensive patients (Cottone et al 1998), young normotensive offspring of hypertensive parents (Mangieri et al 1998) and patients with congestive heart failure (Mangieri et al 1997). On the other hand, we have recently demonstrated that static handgrip caused also an increase in the plasma adrenomedullin (ADM), which is a potent vasorelaxant probably involved in the fine blood pressure control counteracting the effect of vasoconstrictors.…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, the vast majority (76.5%) performed the handgrip, followed by knee extension (13.7%) (Table 1 , Ref. [ 8 , 13 , 18 , 19 , 20 , 22 , 23 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ...…”
Section: Resultsmentioning
confidence: 99%